Answer:
Add a radical term to both sides and square both sides twice.
Explanation:
Given the radical equation
√(b+6) - √b = 5
We are to evaluate the expression for the value of b
Step 1: Add the radical term √b to both sides
√(b+6) - √b +√b = 5+√b
√(b+6) = 5+√b.
Step 2: Square both sides of the equation
(√(b+6))² = (5+√b.)²
b+6 = 25+10√b+ (√b)²
b+6 = 25+10√b + b
Step 3: collect like terms
b+6-b-25 = 10√b
-19 = 10√b
Step 4: square both sides of the resulting equation
(-19)² = (10√b)²
361 = 100b
b = 361/100
b = 3.61
Based on the calculation above, the correct option is C.
Add a radical term to both sides and square both sides twice.